1967
DOI: 10.1149/1.2426592
|View full text |Cite
|
Sign up to set email alerts
|

The Corrosion of 1100 Aluminum in Water from 50° to 95°C

Abstract: OXIDE DISSOLUTION ) unless CC License in place (see abstract). ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 130.184.234.34 Downloaded on 2015-03-16 to IP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

1970
1970
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
2
8
0
1
Order By: Relevance
“…12 Contrarily, activation energies as high as 450 kJ/mol have been reported for the corrosion of aluminum plates in nuclear power plants. 14 These results corroborate to the initial hypothesis that the dissolution of the protective hydroxide layer controls the kinetics of the Al-H 2 O reaction in cement-containing castables.…”
Section: Effect Of Temperaturesupporting
confidence: 85%
“…12 Contrarily, activation energies as high as 450 kJ/mol have been reported for the corrosion of aluminum plates in nuclear power plants. 14 These results corroborate to the initial hypothesis that the dissolution of the protective hydroxide layer controls the kinetics of the Al-H 2 O reaction in cement-containing castables.…”
Section: Effect Of Temperaturesupporting
confidence: 85%
“…Takahashi et al (1990) examined the corrosion of 99.99% pure AI in boiling distilled water and found that essentially no aluminum was lost to the aqueous environment for exposure periods of up to 1 hour. The 95°C data from Draley et al (1967) show little oxide dissolution initiallj, but the fraction of A1 lost to the solution increased with time and reached 15% after 45 days of exposure. As discussed earlier, the fo_xnation of a bayerite film essentially stops dissolution.…”
Section: Aluminum Alloysmentioning
confidence: 97%
“…The bulk of aluminum alloy corrosion data available for distilled water at temperatures less than 100°C are from a series of AI-1100 corrosion studi_s conducted at Argonne National Laboratory (Draley and Ruther 1956a, Draley and Ruther 1956b, Draley 1960, Draley et al 1963; the most directly applicable of these data ,are given in Draley et al (1967). These experiments were conducted at 50, 70 and 95°C…”
Section: Aluminum Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Reaktion von Aluminium mit reinem Wasser ist im Temperaturbereich bis 100 "C eingehend untersucht worden. Pseudobohmit und Bayerit bilden sich zwischen 40 und etwa 80 "C (18,43,54,68). Oberhalb dieser Temperatur entsteht fast ausschlieBlich Bohmit (16), der allerdings gegenuber der Normalzusammensetzung einen stark erhohten Wassergehalt aufweist (8,95).…”
Section: Die Korrosionsprodukteunclassified